ANALISIS PEMBELAJARAN MUATAN PPKN DALAM MEMBENTUK PERILAKU FILANTROPI SISWA KELAS V SD NEGERI BANGUNHARJO BANTUL - Devi Widya Ningsih; Wachid Pratomo; Nadziroh Nadziroh; Chairiyah Chairiyah (JURNAL PEKAN : Jurnal Pendidikan Kewarganegaraan, 2023)
The objectives of this research are (1) To determine the analysis in instilling philanthropic behavior in class V students at SD Negeri Bangunharjo Bantul through PPKn learning, (2) To determine the supporting factors in instilling philanthropic behavior in class V students at SD Negeri Bangunharjo Bantul, (3) To determine the inhibiting factors in instilling philanthropic behavior in fifth grade students at Bangunharjo Elementary School, Bantul. (4) To find out what the solution is to overcome obstacles in instilling philanthropic behavior in class V students at Bangunharjo State Elementary School, Bantul through PPKn learning. This type of research uses descriptive qualitative. The data collection techniques used were observation, interviews and documentation. The data collection instrument uses data analysis techniques with an interactive model, namely data collection, data reduction, data presentation and drawing conclusions. The results of this research show that (1) analysis of cultivating philanthropic behavior requires involvement between the family, school and community. Philanthropic behavior is a stingy attitude and it is difficult to give help. Fifth grade students at Bangunharjo State Elementary School still have a stingy attitude and it is difficult to give help, therefore the cultivation of philanthropic behavior has not gone according to plan. This needs to be corrected by instilling philanthropic behavior in Civics learning so that philanthropic behavior is formed. good, PPKn learning has gone according to plan and can be well received by students, (2) supporting factors from a good family environment as the first place for children to model and emulate, supported by the school environment which provides material reinforcement for instilling behavior philanthropy with the assistance of supervision from a good community environment, (3) inhibiting factors from disharmonious family conditions which can influence children's development in instilling philanthropic behavior, inadequate school environments, and poor community environments will be the main factors in inhibiting the instillation of philanthropic behavior for students, (4) the solution is carried out by collaborating between teachers and parents to provide an understanding of the cultivation of philanthropic behavior at home and during Civics learning activities as well as providing good examples in everyday life so that students are able to instill a positive attitude .Keywords: Civics Learning, Philanthropic Behavior